PENGARUH KOMBINASI DOSIS KOMPOS GULMA DAN PUPUK SINTETIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Suri Dwijaniati Kurnia; Nanik Setyowati; Alnopri Alnopri (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[EFFECT OF WEED COMPOST AND SYNTHETIC FERTILIZER DOSAGE ON TOMATO GROWTH AND YIELD (Lycopersicum esculentum Mill.)]. The growth and yield of tomato plants are influenced by fertilizer and nutrient content in the soil. This study aims to investigate the effect of a combination of synthetic fertilizer and weed compost on the growth and yield of tomato plants. The study was conducted in November 2016 through June 2017 in Agronomy, Faculty of Agriculture, University of Bengkulu, at an altitude of ± 10 m above sea level using a Completely Randomized Design (CRD). The treatments consisted of synthetic fertilizer at a rate of 180 kg/ha N, 150 kg/ha P2O5 and 100 kg/ha K2O (control), grass compost 30 , 40 and 50 tons/ha, 50% control + grass compost 15 tons/ha, 50% control + 20 tons/ha grass compost and 50% control + 25 tons/ha grass compost. The results revealed that the vegetative growth of tomato plants fertilized with grass compost 30 tons/ha and a combination of grass compost + 50% control did not differ from control treatment. Tomato yield fertilized with grass compost 30 tons/ha and a combination of 50% control + 15 tons/ha grass compost was higher than the control treatment. Therefore, 15 tons/ha of grass compost can reduce the dose of synthetic fertilizer by 50%.